2019
DOI: 10.3233/jad-180641
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychiatric Inventory in Community-Dwelling Older Adults with Mild Cognitive Impairment and Dementia

Abstract: Background Behavioral and psychological symptoms (BPSD) can be a prodrome of dementia, and the Neuropsychiatric Inventory (NPI) is widely used for BPSD evaluation. Objective To compare the prevalence of BPSD according to cognitive status, and to determine NPI cutoffs that best discern individuals with mild cognitive impairment (MCI) and dementia from those without dementia. Methods We included 1,565 participants (mean age = 72.7 ± 12.2 years, 48% male). BPSD and cognitive status were assessed with the NPI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
23
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 41 publications
3
23
0
1
Order By: Relevance
“…No study has explored the predictive power of MBI in MCI development among CN subjects. The prevalence of NPI symptoms was reported to be 28.4%–85% among MCI subjects 3, 35, 37, 38 . Our pooled MBI prevalence of 45.5% among MCI subjects falls within the previously reported range.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…No study has explored the predictive power of MBI in MCI development among CN subjects. The prevalence of NPI symptoms was reported to be 28.4%–85% among MCI subjects 3, 35, 37, 38 . Our pooled MBI prevalence of 45.5% among MCI subjects falls within the previously reported range.…”
Section: Discussionsupporting
confidence: 86%
“…The Neuropsychiatric Inventory (NPI) was designed to detect behavioural and psychological symptoms of dementia in patients with dementia 34 . Previous studies have used the NPI to study NPS in CN and MCI subjects 3, 18, 35–38 . NPI scores ≥4 are usually considered clinically relevant 1 .…”
Section: Discussionmentioning
confidence: 99%
“…Though, it may be suggested that i) a valid rating of BPSD was incomplete in the reviewed studies by using questionnaires which are not validated in dementia (i.e. BPRS and PANNS), ii) as BPSD occurs mostly in more advanced dementia (Nunes et al, 2019 ), co-occurrence of PTSD in combination with BPSD might have been lower in the population with new-onset dementia (Ball et al, 2009 ). Accordingly, in elaborating the clinical presentation of PTSD in dementia, recurrent assessments of BPSD, with validated instruments (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…We evaluated the correlation between the ABC-DS score and the global CDR score. In a previous study of the ABC-DS, scores of 13–70, 71–85, 86–100, and 101–117 corresponded to global CDR scores of 3, 2, 1, and 0.5–0, respectively [21]. In our study, ABC-DS scores of 13–58, 59–75, and 76–117 corresponded to global CDR scores of 3, 2, and 1, 0.5–0, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…DAD, NPI, CDR, and MMSE have been used to evaluate ADL, BPSD, and cognitive function in various dementias, as well as in diseases that cause dementia symptoms, whereas DLB and FTLD are disease-specific evalu-ation scales. DAD, NPI, CDR, and MMSE are utilized frequently [20][21][22].…”
Section: Discussionmentioning
confidence: 99%